(untitled) (Journal of humanities and social sciences exploratio, 2026)
This paper takes the mirror narrative in Yasunari Kawabata’s "Snow Country" as the research object to explore how it carries and reconstructs the traditional Japanese aesthetics of mourning. The article takes the virtual and real realities formed by car windows, twilight, mirrors, etc. As the starting point and believes that the mirror image has not only become the carrier of the alienation perspective of the protagonist Shimamura, but also a profound aesthetic mechanism. It further explains that the mirror image reflects the relationship between the "image in the mirror" and the "person outside the mirror" between the foal and the leaf, to symbolize the female image as the double embodiment of the beauty of mourning. Finally, it is concluded that Kawabata Yasunari uses this unique mirror device to transform classical mourning into modernity, that is, to capture the fleeting beauty in the illusory gaze, and deepen the sadness and truth of the futility of life and the nothingness of existence in the fragmentation and disappearance of the mirror image.